1992
DOI: 10.1007/bf00130026
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of woody plants in Mediterranean old fields: opportunity in space and time

Abstract: The establishment of woody plants following agricultural abandonment in the Mediterranean region is a very widespread process which underlines the extent of the rural exodus. The installation windows in space and time were studied in the French Mediterranean region for two common woody plants, Buxus sempervirens and Fraxinus angustifolia and for a group of common woody fleshy-fruited species. These plants differ in their principal modes of dispersal which are respectively, barochory, anemochory and ornithochor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
4

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 48 publications
4
62
0
4
Order By: Relevance
“…The first evidence that runoff may act as a vector of seed transport was indirect and based on observations of seed dispersal strategies in runoff-prone areas (Friedman and Orshan, 1975;Friedman and Stein, 1980), comparisons of plant distribution with different dispersal mechanisms between slopes and wadis (Reichman, 1984), or descriptions of seed distribution patterns in different microhabitats (Ellner and Schmida, 1981) in desert ecosystems worldwide. In the 1990s, it was argued that seed removal by runoff led to seed loss and might explain the lack or scarcity of vegetation on semiarid and arid hillslopes (Debusche and Lepart, 1992;Francis, 1991;Chambers and Mac Mahon, 1994). Although frequently invoked, this assumption was not empirically checked until the pioneering studies of García-Fayos and his collaborators about seed transport by runoff flow.…”
Section: Conceptual Model Of Seed Fates and Movements In And On The Soilmentioning
confidence: 99%
“…The first evidence that runoff may act as a vector of seed transport was indirect and based on observations of seed dispersal strategies in runoff-prone areas (Friedman and Orshan, 1975;Friedman and Stein, 1980), comparisons of plant distribution with different dispersal mechanisms between slopes and wadis (Reichman, 1984), or descriptions of seed distribution patterns in different microhabitats (Ellner and Schmida, 1981) in desert ecosystems worldwide. In the 1990s, it was argued that seed removal by runoff led to seed loss and might explain the lack or scarcity of vegetation on semiarid and arid hillslopes (Debusche and Lepart, 1992;Francis, 1991;Chambers and Mac Mahon, 1994). Although frequently invoked, this assumption was not empirically checked until the pioneering studies of García-Fayos and his collaborators about seed transport by runoff flow.…”
Section: Conceptual Model Of Seed Fates and Movements In And On The Soilmentioning
confidence: 99%
“…In our study sites, P. sylvestris was one of the two main pioneer woody species. Debussche & Lepart [41] and Debain [42], working on this species, showed that its principal front of colonisation was situated a few tens of meters around old pine stands, and individuals that have become established ahead of the colonisation front of old pine stands colonise the space around them. Here, the maturity of the woody populations that were present prior to 1946 permitted the colonisation of heathland relatively quickly.…”
Section: Discussionmentioning
confidence: 99%
“…fruticosus et surtout de Pteridium aquilinum. Ces processus ont cgalemcnt etc reconnus dans des successions en region mediterraneenne (Debussche et al, 1982(Debussche et al, , 1985(Debussche et al, , 1992 Fig. 5 pour Quercus robur) transforme en quelques annees un paysage de friches ou de prairies en un paysage preforestier, voire forestier.…”
Section: Discussionunclassified
“…Mais il est evident qu'une partie non negligeable des diaspores, notamment ceUes des especes ligneuses, resulte d'apports exterieurs, notamment dans le contexte bocagcr. II s'agit de processus competitifs par interference, c'est-a-dire d'une interaction directe entre individus qui recherchent activement ce que d'autres utiliscnt dans un pool commun de ressources (Connell, 1990;Debussche et Lepart, 1992).…”
Section: Discussionunclassified